If \( A=m^{2}-9 m \) and \( B=1-9 m^{2} \), find an expression that equals \( 2 A-B \) in standard form.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
Let's start by substituting the given expressions for \( A \) and \( B \) into the expression \( 2A - B \): 1. First, compute \( 2A \): \[ 2A = 2(m^2 - 9m) = 2m^2 - 18m \] 2. Now, substitute for \( B \) and compute \( 2A - B \): \[ B = 1 - 9m^2 \] \[ 2A - B = (2m^2 - 18m) - (1 - 9m^2) \] 3. Distributing the negative sign in front of \( B \): \[ 2A - B = 2m^2 - 18m - 1 + 9m^2 \] 4. Combine like terms: \[ 2A - B = (2m^2 + 9m^2) - 18m - 1 = 11m^2 - 18m - 1 \] The expression that equals \( 2A - B \) in standard form is: \[ \boxed{11m^2 - 18m - 1} \]